THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND STORE ATMOSPHERE TOWARDS CUSTOMER REPURCHASE INTENTION AT FAT-FAT RESTAURANT IN BEKASI - Kezia Kezia; J.E. Sutanto; Moses Soediro; Adrie Oktavio (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Research entitled "The influence of product quality, service quality and store atmosphere towards customer repurchase intention at Fat-Fat Restaurant in Bekasi" has four objectives, namely: (1) Knowing the influence of product quality towards customer repurchase intention, (2) Knowing the influence of service quality towards customer repurchase intention , (3) Knowing the influence of store atmosphere towards customer repurchase intention, (4) Knowing the influence of product quality, service quality and store atmosphere simultaneously towards customer repurchase intention. Fat-Fat restaurant is a business engaged in the culinary field that offers Chinese food. This study uses quantitative research methods. The population in this study are all consumer who have bought Fat-Fat Restaurant product more than once. The sample of this study amounted to 210 respondents. Dat was collected using questionnaire that distributed online and offline. The data of this study were obtained using multiple linear analysis using the IBM SPPS 25 program as a tool. The results of this study are: (1) Product quality significantly influences customer repurchase intention (2) Service quality significantly influences customer repurchase intention (3) Store atmosphere significantly influences customer repurchase intention (4) Product quality, service quality and store atmosphere are simultaneous against customer repurchase intention. Keywords: product quality, service quality, store atmosphere, customer repurchase intention.